Extracellular enzyme kinetics and thermodynamics along a climate gradient in southern California. (November 2017) - Baker, Nameer R.; Allison, Steven D.
Abstract: Microbial decomposers produce extracellular enzymes to degrade complex plant polymers, making plant C available for metabolism and eventual respiration back to the atmosphere as CO2 . Knowledge of how extracellular enzyme kinetics and microbial activity vary with climate is therefore valuable for predicting how future carbon cycling may be affected by climate change, but studies investigating such dynamics in more xeric ecosystems are underrepresented in the literature. We investigated how microbial biomass, litter chemistry, and extracellular enzymes (Vmax and Km ) and their temperature sensitivities varied along a Mediterranean climate gradient in southern California. Total microbial biomass did not vary among sites along the gradient in either the dry or the wet season. In contrast, extracellular enzyme Vmax and Km varied as a function of fungal biomass and substrate availability. We also found that Vmax of most enzymes was more sensitive to temperature in colder sites than in warmer sites, though only in the dry season. In contrast, Km of multiple enzymes was more sensitive to temperature in warmer sites across both seasons. Observed enzyme Vmax and Km were indicative of extracellular enzyme accumulation in the drier sites along the gradient, which may contribute to the large pulses of respiration that follow rewetting events in these xeric systems. Variation in enzyme characteristics along the gradient indicate that as these systems become more arid in the future, enzyme dynamics will shift from smaller, potentially more active pools to larger, potentially less active enzyme pools that accumulate over dry periods. In addition, rates of enzymatic decomposition will likely be most sensitive to rising temperatures in the coldest sites along our gradient. Highlights: Extracellular enzyme Vmax, Km, and temperature sensitivity vary with climate. Fungal biomass, proteolytic activity and substrate availability explain Vmax, Km . Vmax and Km exhibited positive temperature sensitivity along the gradient. Temperature sensitivity may seasonally depend on site mean annual temperature.